Rural-urban difference in plasma lipid levels in acute myocardial infarction patients of zaporizhzhia region - Yechuri, Ravindra; Syvolap, V. D.; Сиволап, Віктор Денисович; Lashkul, D. A.; Лашкул, Дмитро Андрійович (Запорізький державний медичний університет, 2019)
Introduction. Atherosclerosis is one of the main leading modifiable cause of acute myocardial infarction which is due to dyslipidemia meaning increased triglycerides or low density cholesterol and/or decreased high density cholesterol. The lifestyle plays an important role in the alteration or maintenance of one’s lipid profile. Aim. To determine the lipid levels in rural and urban population in acute myocardial infarction (AMI) patients of Zaporizhzhia region. Material and Methods. A cross-sectional study is performed by collecting the data which is the lipid profile, place of residence (that is urban or rural) of the patients admitted in Cardiology Department Regional cardio-vascular center of Zaporizhzhia. Patients are selected randomly who meet the following mentioned criteria. The criteria being: the patient should be diagnosed with AMI. The patient’s place of residence should be within the territory of Zaporozhzhia region. The patient’s case history should contain the lipid profile. 100 patients are selected who meet the criteria. They are divided into 2 groups in a 1:1 ratio based on their residence, that is 50 patients from the rural areas in Zaporizhzhia state (rural) and 50 patients from Zaporizhzhia city (urban) both men and woman combined. Then they are grouped based on their gender. They are further analysed based on their level of low density lipoproteins (LDL) i.e, level <1.8,>1.8 to <2.6 and >2.6 mmol/l. Statistical analysis was carried out using the statistical software package "Statistica 13.0" (package StatSoft Inc, USA, № license AXXR712D833214FAN5). All data is given in the form of average (M), standard deviation (± SD). The hypothesis about the normality of the distribution of indicators was checked using the Shapiro - Wilk criterion. To compare the statistical characteristics in different groups, with a pairwise comparison of the Mann-Whitney U Test. For the analysis of conjugate tables 2×2, when comparing categorized variables, a two-way exact Fisher or Chi2 test was used.
Keywords: тези доповідей